Evaluation of different plant extracts as a postharvest management strategy for enhancement of shelf life in Tomato fruit - Anjum, Sumreen; Naveed, Zoya; Anees, Moazzam; Sarwar, Mubeen; Mustaq, Zain; Rizwan Tariq, Muhammad; Ashraf, M. Irfan; Gulraiz, Ch. Zain (Journal of Agriculture and Biology, 2024)
Tomatoes are the most commercialized vegetable due their high nutritional content and health-promoting properties. However, tomatoes have a short shelf life; edible coatings have evolved as an effective approach to enhance its shelf life. Edible coatings are thin layers applied onto the surface of fruits and vegetables to improve their physiochemical properties. Different natural extract such as neem leaf extract, lemongrass leaf extract, ginger extract, garlic extract, aloevera gel and distilled water along with control were used as edible coating on shelf life and quality of tomatoes under room temperature. Data was collected on many traits i.e., tomato weight loss, fruit pH, fruit color, total soluble salts (TSS), firmness and total phenolics contents. The treated tomatoes showed significantly minimum weight loss, good appearance, color, firmness and high total phenolics contents. So, these natural and environmental friendly edible coating could be considered a potential postharvest treatment to delay ripening and to conserve the quality of harvested tomatoes. Data was analyzed using LSD test at 5% probability level.
Keywords: Tomato; postharvest management; shelf life; quality traits